Analisis Kelayakan Finansial Usaha Penggilingan Padi “Wadah Rejeki” di Desa Sekarwangi Kecamatan Rawamerta Kabupaten Karawang - Rizki Fauzi; Kuswarini Sulandjari; Suhaeni Suhaeni (Peneliti.net, 2021)
Rice (Oryza sativa) is a the main food crop commodity for Indonesia. Post harvest handing of rice is one of the important factors in increasing value through good quality, including rice milling. The purpose of this study was to: determinethe cost and the “ Wadah Fortune” rice mill business. This research is a quantitative research with primary and secondary data. Data collection techniques: interviews, observatioans, documents and notes. The analytical technique used is financial analysis, with the criteria of Net Present Value, Internal Rate Of Return, Net B/C Ratio, Payback Period and sensitivity analysis. The results of the study: the income obtained by the Wadah Fortune RMU business was Rp. 25.2020.251.543 and the analysis of financial calculations obtained the NPV value Rp. 946.544.956, Net B/C ratio of 2.87, IRR 19% and payback periode of 4 years. This means that the Wadah Fortune milling business is feasible to run. Sensitivity analysis if the production decrease by 10% results in an NPV value of Rp. 184.142.380, IRR 8% is still considered feasible, but the Net B/C ratio of -1.23 is not feasible while the PP (payback periode) gets 7 years. Sensitivity analysis of a 15% decrease in selling price results in NPV value of -Rp638.010.469, a Net B/C Ratio of -0.97 and IRR of -28% and a 13 year PP (Payback Periode) is not feasible.